10 years of Outcome Mapping - and Smith, R; Mauremootoo, John; Ambrose, K.; Hearn, Simon (2012)
This webinar from the Outcome Mapping Learning Community (OMLC) presents the key findings from research conducted into the extent of Outcome Mapping use and the support required for its implementation.